The Differential Nature of Remote Learning Among University Students - Salmani, Khosro; Conley, Joel; Uzoka, Chidera (Imagining SoTL, 2024)
One of the many drastic effects of the COVID-19 pandemic in early 2020 was a sudden shift to remote learning for post-secondary students. Remote learning is an ongoing practice at many educational institutions, for which the impact on students is yet to be understood. This study aims to build a foundation for that understanding, with a particular focus on addressing the effects on students who were working concurrently with their studies during the pandemic. A survey was conducted, gathering 181 responses from undergraduate computing students attending Mount Royal University. The survey queried the students’ experience with work-school balance during the pandemic, their feelings about online classes, the perceived positive and negative aspects of learning online, and whether they would choose online classes in the future in the absence of any pandemic-related concerns. The results show a clear perception of increased flexibility (88%) coupled with an increase in the students’ ability to manage their time (61%). Given that 74% of respondents report that online classes are more convenient than in-person classes while only 22% report a negative impact on their performance, this study concludes that online learning opportunities may correlate with an easing of stress on post-secondary students without significantly impacting academic performance for certain personality types. However, other students report negative experiences with respect to their mental health.